Pemahaman Hadis dan Resepsi Kultural Tradisi Upacara Nadran (Sedekah Laut) di Muara Angke, Penjaringan – Jakarta Utara - Ade Fakih Kurniawan; Salim Rosyadi; Siti Anggiaty Supriatna (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Indonesian society has inherited traditions from its predecessors to fulfill environmental behavioral requirements. However, some traditions or habits are less popular and disappear on their own. One of the traditions in Indonesia is the Nadran tradition in Muara Angke, North Jakarta. In Islam, there are various views on this sea alms, making it necessary to review the Nadran tradition more deeply, especially from the perspective of hadith.This study aims to determine how the Nadran tradition is practiced in Muara Angke and how the community understands this tradition. The research method used is field research, collecting information related to the Nadran tradition.The results show that the Nadran tradition is practiced by the Muara Angke community every year on the Prophet's Birthday. The study's findings provide insights into the community's understanding of the Nadran tradition and its significance in Indonesian culture. The basis of the hadith used in this tradition is the hadith narrated by al-kuttub as-sittah.